Charge transport comparison of FA, MA and Cs lead halide perovskite single crystals for radiation detection - Bennett, Stephanie H.; Ghosh, Joydip; Gros-Daillon, Eric; Lédée, Ferdinand; Mayén Guillén, Javier; Verilhac, Jean-Marie; Zaccaro, Julien; Chung, Duck Young; Klepov, Vladislav; Kanatzidis, Mercouri G.; Sellin, Paul J. (Frontiers in Detector Science and Technology, 2023)
We report a systematic comparison of the charge transport and radiation detection properties of inorganic and organic metal bromide single crystal perovskites. We studied the performance of Bridgman-grown CsPbBr 3 single crystals, together with solution-grown FAPbBr 3 and MAPbBr 3 single crystals. Laser time of flight is used to measure the drift mobilities for all samples, and we report a maxium mobility value of 121 ± 10 cm/Vs for CsPbBr 3 . Alpha particle measurements were used to assess the mobility-lifetime products, with values recorded in the range of 2x10 −4 cm 2 /V to 1x10 −3 cm 2 /V. Low temperature measurements showed an increase in bulk resistivity at temperatures down to 260 K, but no significant change to the drift mobilities. The overall performance of the Cs, FA and MA samples is compared and their potential for use in gamma spectroscopy measurements is discussed.